(untitled) (Functional Plant Breeding Journal, 2022)
Resumo em inglês* Abstract: The case of a 60-year-old male patient, female sequel, will present physiotherapeutic care with after a Stroke and cenile studies of hydrocephalus, with the objective of studying the physiotherapeutic approach in their clinical manifestations. Introduction: Neuropathy is a pathology that acts directly on the peripherals, and can affect and affect cerebellar motricity, it is defined as a lesion in the brain, whereas the sensory, loss of coordination of movements, as well as the organization for its execution, consequently impairing the muscle tone and balance. Methodology: Articles from Pubmed, Medline and other databases were used as references for the case study, in addition to following data from the Brazilian Association of Technical Standards (ABNT). Objectives and results: Aspects of neuropathy were identified and since it is a systemic or traumatic one that damages nerve cells, causing dysfunction of sensations; as a perspective about the beauty and the verification of several dysfunctions that she has, among them, balance and motor coordination; and the physiotherapy of cerebellar ataxia as a clinical manifestation of neuropathy and it was found that it is fundamental in these cases, since its function is to obtain an improvement in motor coordination, gait, balance, posture, and mobility, encouraging the patient to be in the best possible shape in your daily activities environment. Conclusion: The physiotherapeutic treatment obtained a great clinical advance, in view of its gait, balance, muscle tone and motor coordination, promoting quality of life and reducing the risk of falling through physiotherapeutic conducts based on kinesiotherapy.